Evidence and gaps in clinical outcomes of novel pharmacologic therapies for sickle cell disease: A systematic literature review highlighting insights from clinical trials and real-world studies - Mohamed Yassin (4166515) (2025)
This systematic review aims to summarise the clinical outcomes of l-glutamine, crizanlizumab, and voxelotor in the treatment of sickle cell disease (SCD) based on clinical trials and real-world data and to identify any gaps in the observations. The review identified 97 studies reporting data until 31 May 2024. A pivotal phase III study of l-glutamine showed that patients treated with l-glutamine had a 25 % reduction in pain crises and 33 % fewer hospital days compared to placebo. l-glutamine was generally well tolerated with minimal side effects. Real-world studies of l-glutamine emphasize patient adherence and obstacles to medication accessibility and approval as key concerns. In the SUSTAIN study, a 5-mg/kg dose of crizanlizumab reduced the occurrence of vaso-occlusive crises (VOCs) and hospitalizations by 45 % and 41 %, respectively. Real-world studies of crizanlizumab showed a reduction in complicated VOC events. The high discontinuation rate and results of the STAND trial led to a significant decrease in the use of crizanlizumab. The HOPE trial demonstrated a 51 % improvement in hemoglobin response and a reduction in hemolytic markers in patients treated with voxelotor. While some real-world studies have reported a decrease in VOCs and hospitalizations, the results are inconsistent and not conclusive. Further studies are needed to assess the impact of these novel therapies on end-organ-specific complications of SCD. Other Information Published in: Blood Reviews License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.blre.2025.101298